Meta-analysis of BCOR rearranged sarcomas: challenging the therapeutic approach. (3rd June 2021) - Kyriazoglou, Anastasios; Bagos, Pantelis
Abstract: Introduction: BCOR rearranged sarcomas comprise a group of malignant mesenchymal tumors that until recently were classified as Ewing sarcomas or as undifferentiated round cell sarcomas. The identification of alterations involving BCOR gene such as BCOR-CCNB3, BCOR-MAML3, ZC3H7B-BCOR fusion genes and BCOR internal tandem duplication (ITD) is characteristic for the differential diagnosis of BCOR rearranged sarcomas. Due to the rarity of these tumors there is no consensus or guidelines regarding the optimal therapeutic algorithm, that clinicians should follow. Patients and methods: Herein we have conducted a meta-analysis of the current reports dealing with the therapeutic approach of BCOR rearranged sarcomas. Results: Meta-analysis of the 57 eligible cases from 10 studies resulted to similar Incidence Rate Ratio (IRR) and overall survival (OS) for patients who received Ewing protocols and non-Ewing oriented treatment. Further similar death rate was reported for both strategies (non-Ewing 20% Vs Ewing 21.8%). Conclusion: Our data support that non-Ewing treatment strategy can be considered a safe option, being at least equal to Ewing protocols. The current study provides a hint toward the optimal therapeutic approach of BCOR rearranged sarcomas. Further, the present study challenges the use of the term Ewing-like sarcomas, since the current literature supports that BCOR rearranged sarcomas deserve their own distinct classification in terms of genetics, pathology and therapy.